Four research pathways for understanding the role of smart technologies in accounting. Issue 5 (11th August 2021) - Mancini, Daniela; Lombardi, Rosa; Tavana, Madjid
Abstract : Purpose: This paper aims to study the role of smart technologies (e.g., artificial intelligence, Internet of Things, blockchain and analytics, among others) in the accounting environment (AE). In this context, the nuances of innovation generated by such technologies allow for tracing the merging trends in accounting research. Design/methodology/approach: This paper uses an integrated qualitative methodology composed of structured literature analysis and systematic literature analysis to study scientific papers published and stored in prominent databases from 2000 to 2020. This paper collected a data set sharing topics related to smart technologies and innovation in the AE. Findings: The primary findings reveal four research paths of innovation, impact, implication and intelligence in accounting research as follows: smart technologies as innovations to be managed; smart technologies as impacting tools affecting the AE in certain circumstances; smart technologies as a source generating relevant implications; and smart technologies as factors requiring new and updated knowledge, skills and abilities of actors. Originality/value: The joint investigation of the AE and smart technologies poses a milestone for future academic and professional accounting research. This paper proposes a new framework (SMATECHacc Framework) consisting of four pathways research that can be used by future researchers to consider and construct their own research designs.